KERJASAMA INDUSTRI KREATIF ANTARA ISMAYA DENGAN ELROW (SPANYOL) DALAM MENUMBUHKEMBANGKANG INDUSTRI LOKAL: STUDI KASUS DJAKARTA WAREHOUSE PROJECT PERIODE 2016-2018 - Muhammad Sufi Fariduddin (2020)
The movement of an era makes a variety of new things emerge and becomes a new movement for every actor in the international world. Creative Industries emerged as a new movement in the industrial field of a country to be able to achieve power or an economic strategy for countries in the international world. One of the creative industry activities namely the Djakarta Warehouse Project (DWP) is a creative industry in Indonesia and is internationally renowned. DWP itself is one of the products of Ismaya company which is a non-state actor and activist of the Indonesian creative industry. Various kinds of culture and identity of the country which is famous for its diversity, namely Indonesia, is poured into a music event which is a product of Ismaya company. Starting from Garuda which was introduced to the international community and Ondel-Ondel art which became a special attraction when the music event was held in the Kemayoran region. This event also successfully boasted the country of Indonesia by becoming the largest EDM music event in Asia. Collaboration between creative industry activists namely Ismaya and Elrow has become a special attraction in DWP music events. Elrow is a non-state actor in the field of creative industries from Spain. Collaboration between the two non-state actors has an impact and effect on a variety of local industries.